Medicated-related burden and adherence in patients with co-morbid type 2 diabetes mellitus and hypertension. Issue 4 (April 2023) - Baah-Nyarkoh, Emmanuella; Alhassan, Yakubu; Dwomoh, Andrews K.; Kretchy, Irene A.
Abstract: Background: Medication adherence is an integral component in the management of patients with co-morbid type 2 diabetes mellitus (T2DM) and hypertension. However due to their combined conditions, there is likelihood of polypharmacy and medication-related burden, which could negatively impact adherence to therapy. This study aimed to assess the perceived medication-related burden among patients with co-morbid T2DM and hypertension and to evaluate the association between the perceived burden and adherence to medication therapy. Methods: A cross-sectional study was conducted among adult patients with co-morbid T2DM and hypertension attending a primary health facility. The living with medicines questionnaire and the medication adherence report scale were used to assess extent of medication-related burden and adherence respectively. Binary logistic regression model was used to estimate the adjusted odds and their corresponding 95% confidence interval for medication-related burden and adherence outcomes. All observed categorical variables were considered for the multivariable binary logistic regression model. Results: The total number of participants was 329 with a median age of 57.5 ± 13.2 years. The median score for the overall burden was 99 (IQR: 93–113), and this significantly varied by sex (p = 0.012), monthly income (p = 0.025), monthly expenditure on medications (p = 0.012), frequency of daily dose of medications (p = 0.020) and family history of T2DM (p < 0.001). About 30.7% and 36.8% of participants reported moderate/high burden and medication adherence respectively. Uncontrolled diastolic blood pressure (AOR: 2.46, 95% CI: 1.20–5.05, p = 0.014), high glucose (AOR: 4.24, 95% CI: 2.13–8.46, p < 0.001) and no family history of T2DM (AOR: 2.14, 95% CI: 1.14–4.02, p = 0.026) were associated with moderate/high medication burden. Uncontrolled diastolic blood pressure (AOR: 0.48, 95% CI: 0.25–0.94, p = 0.031), at least 5 years since hypertension diagnosis (AOR: 0.55, 95% CI: 0.30–0.99, p = 0.045) and moderate/high medication-related burden (AOR: 0.33, 95% CI: 0.16–0.69, p = 0.003) were associated with lower odds of medication adherence. Conclusion: These findings suggest that to improve the preventive and optimal care of patients with T2DM and hypertension, interventions that aim to reduce medication-related burden and morbidity are recommended. The study proposes that health stakeholders such as clinicians, pharmacists, and policy makers, develop multidisciplinary clinical and pharmaceutical care interventions to include provision of counselling to patients on adherence. In addition, developing policies and sensitization activities on deprescribing and fixed-dose drug combinations aimed at reducing medication-related burden, while promoting better adherence, blood pressure and blood glucose outcomes are recommended.